The implementation of small group discussion in teaching writing recount text for the tenth grade students of SMKN 1 Bendo - Intan Dwi Lestari (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
The goals of this research are to describe the implementation, advantages and disadvantages, and the solution of disadvantages in teaching writing Recount text by using Small Group Discussion. The research uses descriptive qualitative research as approach and type of research. The sources of data are social situation, participant or informant, and document. The technique of collecting data uses observation, interview, and documentation. To know the validity of the data, the researcher uses triangulation. The technique of data analysis are data condensation, data display, conclusion and verification. The result of the research are (1) The implementation of Small Group discussion in teaching writing Recount text divided into (a) Pre-activity which covers greeting, praying, checking attendance list and explaining the purpose of the learning, (b) Whilst-activity covers the explanation the stages of the technique, (c) Post-activity include reviewing and making resume of the material, (2) The advantages are easy to implement in the class and can be understood well by the students, effective to teach types of text, increased participation, make student more intimate with their friend, (3) The disadvantages are student need more times to write, they are difficult in translate the word, disability of implementing correct structure makes some of students did not participate, students’ motivation of writing is still low, take long time because there are four stages that should be done by the students, (4) The solution of the disadvantages are teacher gives clear and simple explanation about the material, asks students to bring the dictionary, explains the role of each member of group clearly, makes the activity into simple one, gives additional time, student aware to other students, and teacher gives a bit of joke or humour and motivation in the process of learning. Based on the result, the conclusion of this research are suitable with the lesson plan, observation, and teaching process in the class. The suggestions are presented for teacher should have variety of strategy in teaching writing, students are suggested to increase their vocabulary, and other researcher are suggested to fulfil the need of the knowledge from other point of view.